Security, Privacy, and Applied Cryptography Engineering : 9th International Conference, SPACE 2019, Gandhinagar, India, December 3–7, 2019, Proceedings /: 9th International Conference, SPACE 2019, Gandhinagar, India, December 3–7, 2019, Proceedings. (2020) - Unknown
No abstract available